LEGAL ANALYSIS OF DIRECTORATE GENERAL CUSTOMS DECISIONS AT EAST JAVA REGIONAL OFFICE I: The Objection of Customs Rate Assessment and Value of PT. Sinar Harapan Berkarya - Ngaisah, Siti; Sani, Alfrida Mutiara (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2022)
The procedure for submitting an objection to the SPTNP (Letter Determination of Tariffs and/Customs Value) is regulated in the Regulation of Director General of Customs Per-15/BC/2017 concerning on Procedures for Filing and Settlement of Objections in the Customs and Excise Sector. The submission of objection to SPTNP PT. Sinar Harapan Berkarya, often get rejection from Director General of Customs. This study implements 2 problems of study, 1. How to grant the objection to tariffs and/or customs value (notul) at PT. Sinar Harapan Berkarya? 2. What is the reason on the objection of tariffs and/customs value (notul) of PT. Sinar Harapan Berkarya being rejected? This study aims to determine the obstacles of rejecting SPTNP objection and find out the conditions for SPTNP objection to be granted by Director General of Customs. This method uses empirical juridical research. This research examines legal provisions and what happens in field or in reality. The discussion includes the requirements for the fulfillment of SPTNP objection, the issuance of SPTNP, the calculation of Customs Tariffs and Values, the method of filing SPTNP objection, the factors that causes the rejection to the Tax Court and Analysis regarding the Decision of Customs General Director. Based on the analysis of objection, there is an inconsistency on the submitting method the Decree of the Director General of Customs.